Rapid microwave-assisted transesterification of yellow horn oil to biodiesel using a heteropolyacid solid catalyst - Zhang, Su; Zu, Yuan-Gang; Fu, Yu-Jie; Luo, Meng; Zhang, Dong-Yang; Efferth, Thomas (Bioresource technology, 2010)
An efficient microwave-assisted transesterification (MAT) technique was developed to prepare biodiesel from yellow horn ( Xanthoceras sorbifolia Bunge.) oil with a heteropolyacid (HPA) catalyst namely Cs 2.5H 0.5PW 12O 40. A study for optimizing the reaction conditions such as reaction temperature, time, molar ratio of methanol/oil, catalyst amount, and recycle number of catalyst has been performed. The maximum yield of fatty acid methyl esters (FAMEs) reached 96.22% under optimal conditions of temperature 60 °C, 10 min, molar ratio of methanol/oil 12:1, 1% (w/w of oil) catalyst and minimum recycle number nine times. The final product of biodiesel, obtained after the new catalyzed process, was analyzed by gas chromatography. The results showed that the Cs 2.5H 0.5PW 12O 40 heterogeneous acid catalyst had higher efficiency for transesterification under microwave irradiation compared with the conventional method. The product properties of yellow horn biodiesel are found to be in agreement with EN 14214 standard.